The Influence Of The Integration Of Digital Literature Books And Recitation Methods On The Development Of Critical Thinking Abilities And Self-Confidence In Middle School Students In Social Studies Learning - Setyorini Titik (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2024)
The main objective in this research is to improve students' critical thinking and self-confidence in learning social studies subjects. Critical Thinking and Confidence in learning social studies subjects as a whole. The role of social studies teachers in using the Resitation Learning Method using Digital Literature Book shows the importance of real context according to the situation in the environment by the students themselves in Critical Thinking and enthusiasm in identifying problems in learning so that the concepts received by students are more meaningfulData in this study are quantitative data obtained from tests of students' knowledge and understanding through questionnaire tests. The results of the percentage of success of this study show: (1) The effect of the Resitation Learning Method using Digital Literature Book on students' critical thinking is 86.6%, (2) The effect of the Resitation Learning Method using Digital Literature Book on students' self-confidence is 91.2%, and (3) The effect of the Resitation Learning Method using Digital Literature Book on students' critical thinking and self-confidence together is 90.0%. This means that the application of the Resitation Learning Method Using Digital Literature Book in increasing Critical Thinking and student confidence in learning social studies subjects is very influential and produces significant results